A Dictionary of Economics - Black, John, 1931-, author 528683 (Oxford ; New York : Oxford University Press, 2003)
"Review from previous edition John Black's dictionary provides clear and concise explanations...An excellent system of cross-referencing the various entries is a valuable aspect... this book is strongly recommended as a handy work of reference for any non-economist who wants to have a better idea about what is going on in economic debates...this book deserves to sell well to a wide audience...it illuminates in a concise and accessible way many of the words and ideas used both in economics itself and in practical political debates on the subject."--